Development of Student Worksheets (LKPD) Based on Problem Based Learning (Pbl) on The Material of Transport and Exchange of Substances in Humans, Phase F SMA/MA - Sri Wahyuni; Ade Dewi Maharani; Vivi Fitriani (Florea : Jurnal Biologi dan Pembelajarannya, 2025)
In the learning process, teaching materials and LKPD are needed to train students' abilities in learning. However, the teaching materials used are not yet appropriate due to the lack of material in the textbooks, in addition, the number of textbooks is still limited, resulting in less effective learning. This will certainly be less effective learning because the textbooks or printed books provided by the school do not match the number of students. This supports the LKPD research which will later become one of the new teaching materials by teachers and students because by using LKPD, learning time can be optimized well and by using LKPD students will be easier in the learning process. The purpose of this study is to produce LKPD Based on Problem Based Learning (PBL) on the material of transport and exchange of substances in humans for SMA/MA which is valid and practical. The development research uses the 4D model. This model has four stages of development, namely the define , design , develop and disseminate stages . This research was conducted until the develop stage , namely the validity test and practicality test. The assessment instruments carried out at this stage consisted of validity and practicality questionnaires, this validity questionnaire consisted of content feasibility, language, didactical, and graphical, while the practicality questionnaire consisted of ease of use, benefits. The data were analyzed using percentage techniques and processed using descriptive analysis or determining the highest score and the final value of validity and practicality. Based on the results of the research test, the developed LKPD is very valid with a value of (89%), the results of the practicality test by 2 biology teachers on the developed LKPD are very practical (92%), and the practicality of 31 students is very practical (87%). Based on the results of the validity and practicality tests, it can be concluded that the student worksheet (LKPD) based on problem based learning (PBL) on the material of transport and exchange of substances in humans for phase f of SMA 1 Akabiluru Kab. Lima Putuh Kota which was developed is very valid and practical.